EXPLORING THE IMPACT OF HIGHER EDUCATION AND POVERTY ON HUMAN DEVELOPMENT ACROSS INDONESIAN PROVINCES 2018-2022 - Lubis, Nabilah Fitri; Nurjanah, Siti; Pratama, Aditya (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study explores the impact of higher education participation and poverty on human development across Indonesian provinces from 2018-2022. Human development is measured by the human development Index (HDI), Which reflects key aspects of well-being, including education, health, and income. A quantitative approach was employed using panel data regression analysis based on 170 observations from 34 provinces over a five-year period, obtained from the Central Statistics Agency. Higher education participation is measured by the gross enrollment rate in higher education, poverty by the percentage of the population living below the poverty line, and human development by the Human Development Index (HDI). The results of the study indicate that Higher Education Participation has a significant positive effect on Human Development, while poverty has a significant negative effect on human development. The R-squared value indicates that 39.3% of the variation in Human Development can be explained by these two variables, while the remainder is influenced by other factors outside the model. The contribution of this study lies in providing the latest empirical evidence that strengthens the position of higher education as a long-term strategy in human resource development.